Proteomic analyses of nucleus laminaris identified candidate targets of the fragile X mental retardation protein. Issue 15 (24th July 2017) - Sakano, Hitomi; Zorio, Diego A. R.; Wang, Xiaoyu; Ting, Ying S.; Noble, William S.; MacCoss, Michael J.; Rubel, Edwin W; Wang, Yuan
Abstract: The avian nucleus laminaris (NL) is a brainstem nucleus necessary for binaural processing, analogous in structure and function to the mammalian medial superior olive. In chickens ( Gallus gallus ), NL is a well‐studied model system for activity‐dependent neural plasticity. Its neurons have bipolar extension of dendrites, which receive segregated inputs from two ears and display rapid and compartment‐specific reorganization in response to unilateral changes in auditory input. More recently, fragile X mental retardation protein (FMRP), an RNA‐binding protein that regulates local protein translation, has been shown to be enriched in NL dendrites, suggesting its potential role in the structural dynamics of these dendrites. To explore the molecular role of FMRP in this nucleus, we performed proteomic analysis of NL, using micro laser capture and liquid chromatography tandem mass spectrometry. We identified 657 proteins, greatly represented in pathways involved in mitochondria, translation and metabolism, consistent with high levels of activity of NL neurons. Of these, 94 are potential FMRP targets, by comparative analysis with previously proposed FMRP targets in mammals. These proteins are enriched in pathways involved in cellular growth, cellular trafficking and transmembrane transport. Immunocytochemistry verified the dendritic localization of several proteins in NL. Furthermore, we confirmed the direct interaction of FMRP with one candidate, RhoC, by in vitro RNA binding assays. In summary, we provide a database of highly expressed proteins in NL and in particular a list of potential FMRP targets, with the goal of facilitating molecular characterization of FMRP signaling in future studies. Abstract : Using micro laser capture and mass spectrometry, we provide a list of putative fragile X mental retardation protein targets specific to an auditory structure important for binaural processing. As verified by immunocytochemistry and RNA binding assays, these targets are potential players in the abnormal auditory processing of fragile X syndrome.